A Modified Rabbit Ulna Defect Model for Evaluating Periosteal Substitutes in Bone Engineering: A Pilot Study - El Backly, Rania M.; Chiapale, Danilo; Muraglia, Anita; Tromba, Giuliana; Ottonello, Chiara; Santolini, Federico; Cancedda, Ranieri; Mastrogiacomo, Maddalena (Frontiers in Bioengineering and Biotechnology, 2015)
The present work defines a modified critical size rabbit ulna defect model for bone regeneration in which a non-resorbable barrier membrane was used to separate the radius from the ulna to create a valid model for evaluation of tissue-engineered periosteal substitutes. Eight rabbits divided into two groups were used. Critical defects (15 mm) were made in the ulna completely eliminating periosteum. For group I, defects were filled with a nanohydroxyapatite poly(ester urethane) scaffold soaked in PBS and left as such (group Ia) or wrapped with a tissue-engineered periosteal substitute (group Ib). For group II, an e-PTFE (GORE-TEX®) membrane was inserted around the radius then the defects received either scaffold alone (group IIa) or scaffold wrapped with periosteal substitute (group IIb). Animals were euthanized after 12-16 weeks, and bone regeneration was evaluated by radiography, computed microtomography (µCT), and histology. In the first group, we observed formation of radio-ulnar synostosis irrespective of the treatment. This was completely eliminated upon placement of the e-PTFE (GORE-TEX®) membrane in the second group of animals. In conclusion, modification of the model using a non-resorbable e-PTFE membrane to isolate the ulna from the radius was a valuable addition allowing for objective evaluation of the tissue-engineered periosteal substitute.